A post-pandemic analysis of career and technical education performance by student gender: A multiyear, Texas investigation - Douglas, Ericca S.; Slate, John R. (American Journal of STEM Education, 2026)
In this statewide, multiyear investigation, Career and Technical Education student participation was examined by gender for the 2020-2021, 2021-2022, and 2022-2023 school years. Statistically significant gender differences were documented in CTE participation rates. Girls had higher overall participation and completion rates compared to boys. Specifically, girls excelled in career clusters such as Health Sciences, Education, and Cosmetology, and were more likely to complete their programs of study. Boys, on the other hand, concentrated more in traditionally male-dominated fields such as Manufacturing, Engineering, and Automotive. However, completion rates for boys were lower, suggesting potential challenges in program persistence. Also determined in this multiyear investigation was overlap in programs such as Accounting and Culinary Arts, where both boys and girls participated at equal rates. Of note, however, was the presence of notable gender differences in other programs of study.